1962
DOI: 10.1113/expphysiol.1962.sp001583
|View full text |Cite
|
Sign up to set email alerts
|

The Absorption of Bound Forms of B‐group Vitamins by Rat Intestine

Abstract: The rates of movement of bound forms of B-group vitamins (coenzyme A, thiamine pyrophosphate, diphosphopyridine nucleotide, flavin mononucleotide and biocytin) from the mucosal to serosal fluids has been measured in everted sacs of rat jejunum. Thiamine pyrophosphate, biocytin and flavin mononucleotide move at approximately the same rates as the free vitamin: there was no indication of active transport. The results thus resemble those obtained with free vitamins alone and suggest that these bound forms are abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1967
1967
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Despite the general interest in the intestinal absorption of these vitamins and coenzyme forms subsequent to their recent clinical uses for therapeutic pur poses, our knowledge is very limited. Even the long dispute of whether vitamin Bl is absorbed after phosphorylation (1, 2), or passively without chemical changes (3), has not as yet been settled, although more recent data suggest active transport across the intestinal mucosa involving phosphorylation (4,5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the general interest in the intestinal absorption of these vitamins and coenzyme forms subsequent to their recent clinical uses for therapeutic pur poses, our knowledge is very limited. Even the long dispute of whether vitamin Bl is absorbed after phosphorylation (1, 2), or passively without chemical changes (3), has not as yet been settled, although more recent data suggest active transport across the intestinal mucosa involving phosphorylation (4,5…”
Section: Discussionmentioning
confidence: 99%
“…adenine dinucleotide, for instance, is broken down into flavine mononucleotide and riboflavin before being absorbed (5,6). Cytidine diphosphate choline (CDP choline) (7) is an important cofactor in the biosynthesis of lecithin, and has come to be used clinically of late.…”
mentioning
confidence: 99%
“…Because they were unable to demonstrate active vitamin transport under their experimental conditions, Turner & Hughes concluded that passive diffu sion (a much less interesting mechanism to physiologists) accounted for intestinal absorption of nicotinic acid, pantothenic acid, biotin, folic acid, and vitamin B12 (113,114). This interpretation was adopted uncritically and found its way into the textbooks, where it reappeared regularly for more than a decade.…”
Section: Historical Perspectivementioning
confidence: 93%